IMPLEMENTASI PENDEKATAN PENDAMPINGAN PRAPERNIKAHAN DALAM PROSES MANGANTAR : STUDI KASUS PADA MASYARKAT SUKU LAUJE - Novanda Yuliana Allow; Natalia Olivia Kusuma Dewi Lahamendu (Institut Agama Kristen Negeri Manado, 2023)
This study aims to examine the origins and meaning of Mangantar from the perspective of multicultural counseling and pastoral culture, examine the implementation of the Mangantar process from the perspective of pastoral and premarital counseling and develop the concept and practice of Mangantar into culturally based media and premarital counseling for the Lauje people. In this research method that will be used is descriptive analytical research, with data collection techniques in the form of interviews and observations. In the interview technique, the author's key informants were the Head of the Lauje Tribe and the Traditional Head, while the supporting informants were people who had carried out the Mangantar tradition. The theory used in this research is multicultural counseling, cultural pastoral and premarital counseling. From the results of the study, it was found that the philosophical foundation and spiritual values ​​of Mangantar, namely sacrifice, responsibility, cooperation, commitment and definition of family, which in the next process will be used as premarital counseling assistance.